Pengaruh Pemberian Metode Thought Stopping dalam Mengurangi Tingkat Kecemasan Akibat Penyakit Fisik Pada Lansiadi Dusun Wayasel Wilayah Kerja Puskesmas Negeri Lima - Hatuwe, Ernawati; Hitiyaut, Mirdat (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of the thought stopping method in reducing anxiety levels due to physical illness in the Wayasel Hamlet, the Working Area of Puskesmas Negeri Lima. This study used a quantitative pre-experimental test using a one-group pre-test-post-test design, the sample in this study amounted to 35 respondents with a sampling technique using purposive sampling with inclusion and exclusion criteria. The research instrument used the HARS questionnaire. Data processing used the Wilcoxon test. The results of this study revealed that there was an effect of the thought stopping method in reducing anxiety levels due to physical illness in the elderly in the Wayasel Hamlet, the Working Area of Puskesmas Negeri Lima